Exploring the diversity and disparity of rhabdodontomorph ornithopods from the Late Cretaceous European archipelago - Łukasz Czepiński; Daniel Madzia (Scientific Reports)
Abstract The origin and early diversification of ornithopods, a major clade of ornithischian dinosaurs, remain poorly understood, with conflicting phylogenetic hypotheses regarding rootward neornithischian relationships. Some topological stability is inferred near the basal divergence of Iguanodontia, though the ingroup relationships remain unclear. For instance, Rhabdodontidae, a clade of Late Cretaceous European ornithopods ‘traditionally’ considered to include eight to nine species, presents significant taxonomic challenges. We explore the diversity and disparity of European Rhabdodon-lineage iguanodontians. We assembled a novel dataset comprising morphological and morphometric data obtained from rhabdodontomorph dentaries, which are abundant, well-preserved in the majority of the taxa, and distinctive. Special attention is given to Rhabdodon septimanicus, a poorly known taxon from the upper Campanian to lower Maastrichtian of southern France, established based on a particularly robust dentary bone that has been subjected to conflicting taxonomic interpretations. Our restudy of the specimen, combined with a multivariate and phylogenetic assessment, shows that this taxon is a clear morphological outlier among European rhabdodontomorphs, providing a basis for its assignment to a new genus, Obelignathus. Although further large-scale studies, especially detailed osteological descriptions, are needed to clarify the taxonomic significance of certain European rhabdodontomorphs, our results indicate that the group exhibits greater diversity than currently recognized, with several sympatric taxa co-occurring, at least in southern France and possibly also in Romania.